(untitled) (Phenomenology, Humanities and Sciences, 2023)
Since the first writings, the thought of Martin Heidegger started to exert a considerable influence on the way of thinking in several areas of knowledge. This article presents how the contributions of Heidegger’s thought influenced the insertion of phenomenology in Geography, focusing on the works carried out within the Humanist Cultural Geography Research Group (GHUM) and the Phenomenology and Geography Research Group (NOMEAR). It is seminal, in this context, the appreciation of the important work “O homem e a Terra”, by the French geographer Eric Dardel, initially published in 1952, as one of the starting points for the rise of the so-called phenomenological geography. With this, we conclude that the reception of Heidegger’s thought took place in a plural form in GHUM and in NOMEAR, and this plurality resulted from the intentionality that moved researchers in their incursions into the geographical experiences they investigated. This did not allow the creation of a new homogenizing “theoretical framework”, but the search for ways to access the phenomena in their differences.